Legal Protection of Employees’ Personal Data under the Saudi Legal Framework - Salma Abubakr Al-Mehdhar (International Journal of Law Research and Studies, 2026)
This study aimed to elucidate the legal protection afforded to employees’ personal data under the Saudi legal framework by clarifying the concept of an employee’s personal data and the employee’s rights in relation thereto, and then by examining the standards and controls governing the collection and processing of such data, the most salient forms of infringement thereof, and the legal consequences arising from such infringement. The study adopted the analytical method through an examination of the relevant provisions of the Saudi Labor Law and the Personal Data Protection Law (PDPL). The study concluded that the regulator has succeeded in striking a balance between the employer’s right to manage its establishment and to access the data of its employees, on the one hand, and the employee’s right to privacy, on the other, by imposing controls and obligations that safeguard the employee’s personal data. It further concluded that infringement of an employee’s data gives rise to criminal liability and administrative liability, in addition to the employee’s right to claim compensation for the material and moral damages sustained as a result thereof. The study recommended the imposition of mandatory training courses for employees whose functions, by their nature, permit them to handle data within the workplace, with a view to ensuring compliance with the controls prescribed by the Personal Data Protection Law.